Christian V's og Frederik IV's politiske testamente - Olden-Jørgensen, Sebastian (Historisk Tidsskrift, 1996)
In the Act concerning Absolute and Hereditary Government of 10 January 1661 (Enevoldsarveregeringsakten) king Frederick 111 (1648-70) made known his intent to regulate several constitutional questions by means of a testament. In early modern Europe a political testament that ordered the succession and gave political guidelines was a common feature of the protestant principalities of the Holy Roman Empire and Sweden. In the end Frederick 111 chose to settle the constitutional question through a written constitution proper: The Royal Law (Lex Regia) of 1665. Both Christian V (1670-99) and Frederick IV (1699-1730), however, wrote political testaments whose purpose was to supplement the general guidelines of the Royal Law with specific political advice about how to maintain the integrity of Danish absolutism. The political testament of Christian V, consisting of four texts written during three periods (1683, 1684, 1698) reflects the king's fear lest absolutism should erode in the vicissitudes of daily administration. Christian V does, however, show a fundamental confidence in his officials whom he kept at bay through an effective divide-and-rule policy. The political testament of Frederick IV from 1723 on the other hand is an urgent and seemingly quite unreasonable warning against using the old Danish and Slesvig- Holstein nobility for any higher office in the military or civil service. Frederick IV evidently feared a military coup. A comparison with the political testament of the Prussian king Frederick Wilhelm (1722) and the Reveries of emperor Joseph II (1763) reveals that a fundamental distrust in the nobility, the »born« partners and antagonists of the rulers, was not so unusual. If the extreme militarization of the Danish-Norwegian state during the Great Northern War is taken into account as well as the personal affairs of the king (the marriage with Anne Sophie Reventlow) the political testament of Frederick IV only seems to reflect the »normal paranoia« of an absolute monarch. The political testament is an expression of personal, dynastic absolutism where the king still very much »is« the state. With the growing importance of the bureaucratic machinery the need for political testaments disappears. In Denmark the reign of Christian VI (1730-46) marks the transition to bureaucratic absolutism.